Democracy in divided societies electoral engineering for conflict management - Reilly, Ben. (Cambridge Cambridge University Press, 2001)
Reilly analyzes the design of electoral systems for divided societies, examining various divided societies which utilize "vote-pooling" electoral systems--including Papua New Guinea, Sri Lanka, Northern Ireland and Fiji. He shows that political institutions which encourage the development of broad-based, aggregative political parties and where campaigning politicians have incentives to attract votes from a range of ethnic groups can, under certain conditions, encourage a moderate, accommodatory political competition and thus influence the trajectory of democratization in transitional states. This is a challenge to orthodox approaches to democracy and conflict management.
Includes bibliographical references (p. 194-214) and index.
Keywords: Elections--Case studies